A Formative Evaluation of Two Evidence‐Based Psychotherapies for PTSD in VA Residential Treatment Programs. Issue 1 (16th February 2013) - Cook, Joan M.; O'Donnell, Casey; Dinnen, Stephanie; Bernardy, Nancy; Rosenheck, Robert; Hoff, Rani
<x xml:space="preserve">Abstract</x> Between July 2008 and March 2011, 38 U.S. Department of Veterans Affairs (VA) residential treatment programs for posttraumatic stress disorder (PTSD) participated in a formative evaluation of their programmatic services, including evidenced‐based treatments (EBTs). Face‐to‐face qualitative interviews were conducted with over 250 staff by an independent psychologist along with onsite participant observations. This evaluation coincided with a national VA dissemination initiative to train providers in two EBTs for PTSD: prolonged exposure (PE) and cognitive processing therapy (CPT). A substantial proportion of eligible (based on professional background) residential treatment providers received training in PE (37.4%) or CPT (64.2%), with 9.5% completing case consultation or becoming national trainers in each therapy respectively. In semistructured interviews, providers reported that their clinical programs had adopted these EBTs at varying levels ranging from no adoption to every patient receiving the full protocol. Suggestions for improving the adoption of PE and CPT are noted, including distilling manualized treatments to essential common elements.